PROPHETIC LEADERSHIP AND IMPLEMENTATION OF STRATEGIC MANAGEMENT OF GREEN NORD 27 BRINGS POSITIVE CHANGES BONEK SUPPORTERS - Moh. Agil Nuruzzaman; Fiona Niska Dinda Nadia (Universitas Dr. Soetomo, 2023)
ABSTRACT This study aims to reveal the facts that have occurred as well as provide another view of the world of football fans, one of the many groups of Bonek supporters named Green Nord 27 (GN'27) in its journey so far there is prophetic leadership and the application of strategic management in changing the old tradition of Bonek supporters who are considered bad to transform for the better. The study approach uses descriptive qualitative methods. Data collection by observation, interviews and documentation. Furthermore, it is analyzed by starting with data collection, validation, reduction and presentation of data until the final conclusion. The location of the study is on Green Nord 27 which is in the city of Surabaya. Informants in this study included: the founders until the coordinators of Green Nord 27, conductors of supporters, members of Bonek supporters and security forces. The results of this study suggest that Green Nord 27 also pioneered the modernization of supporters and became the frontline of changing the dynamics of Bonek supporters towards a positive direction. Interprets amar ma'ruf nahi munkar on two main aspects, namely: wanting to change the bad culture of Bonek supporters so far so that in the future it will change to be more positive and at the moment of fighting for Persebaya by fighting against the arbitrariness of the PSSI federation. The leader or coordinator figures have so far indirectly applied the prophetic leadership breath that is based on the four qualities of the Prophet Muhammad SAW. regarding: siddiq (truthfulness), amanah (trustworthiness), tabligh (advocacy) and fathonah (intelligent) which have a correlation with establishing a truth by fighting evil. The Our Tribune Our Rules campaign from Green Nord 27 also has a contributive impact on other Bonek supporters from year to year. Implementing strategic management processes in realizing goals so far includes: mission statements, environmental analysis, organizational self-assessment, setting goals and objectives until establishing strategies. Keywords: Prophetic Leadership; Strategic Management; Change Management; Green Nord 27